Pulp and paper - Bist, Candice; Aharon, Roni (Environmental awareness, 2000)
This programme traces the search by humans for such a material from pre-history through to the Chinese development of paper - a technology which eventually spread around the globe. The process of making various kinds of paper is described - from rags, from vegetable fiber, and from wood. Viewers also learn how to make and dye their own paper from recycled newspapers. Students visit a commercial tree farm. Finally, the show emphasizes the importance of conversation and reminds viewers to reduce, reuse and recycle.